3PC-022 Preliminary microbiological study of injectable chemotherapy dose-banding. (March 2019) - Dozias, G; Lambert, C; Hugerot, H; Rey-Rubio, B; Loeuillet, C; Mugnier, N; Cogulet, V
Abstract : Background: In our medical centre, the production of injectable ant-ineoplastic rose 20% between 2015 and 2017. As a consequence, the dispensing delay increased. It has therefore been decided to implement dose-banding. In order to guarantee the sterility of preparations after storage, we did a preliminary study of microbiological stability 28 days after making the preparation. Purpose: The study of microbiological stability of injectable chemotherapy produced at an oncological pharmacy after 28 days of storage. Material and methods: We simulated the production of anti-neoplastic preparation with dextrose 5% to avoid chemotherapy contamination at the hygiene laboratory. On day 0, 56 infusion bags were produced in a positive air pressure isolator (Isocyt Freja; Getinge). Half of them were stored at room temperature and the other half at 4°C. Twenty mL samples were taken and inoculated on day 0, 2, 7, 14, 21, 28 and 42 under laminar flow at the pharmacy. This volume represents 10% of the final volume of the bag according to the 2.6.1 chapter of sterility test of the European Pharmacopeia 9.7. Liquid medias used at the hygiene laboratory were thioglycolate and trypticase. Fertility and sterility of these medias were checked. American Type Culture Collection strains were used to test the fertility of these medias. Liquid medias were incubated at the hygiene laboratory for 14 days at 22°C and 34°C.The positivity of the liquid medias was observed by the appearance of a turbidity, visible to the naked eye. Results: Fertility and sterility controls were validated. After 14 days of incubation, no microbiological growths were observed. The main limit of this study was the decision to use one media per bag, to avoid accidental contamination at sampling time. According to a previous study 1 carried out in our medical centre, the majority of the centres that use dose-banding, have only achieved a chemicophysical stability study. Since sterility control cannot be performed systematically, it seemed important to us to prove the microbiological stability of these preparations. Conclusion: This preliminary study proves the sterility of chemotherapy bags after 28 days of storage. It allows dose-banding in order to shorten waiting periods for dispensation. Reference and/or acknowledgements: http://www.gerpac.eu/etat-des-lieux-des-pratiques-du-dose-banding-en-france No conflict of interest.